Internet Searches for Terms Related to Child Maltreatment During COVID-19: Infodemiology Approach - Madelon M E Riem; Pietro De Carli; Jing Guo; Marian J Bakermans-Kranenburg; Marinus H van IJzendoorn; Paul Lodder (JMIR Publications, 2021)
We examined internet searches indicative of abusive parental behaviors before and after the World Health Organization's declaration of COVID-19 as a pandemic (March 11, 2020) and subsequent lockdown measures in many countries worldwide. Using Google Trends, we inferred search trends between December 28, 2018, and December 27, 2020, for queries consisting of "mother," "father," or "parents" combined with each of the 11 maltreatment-related verbs used in the Conflict Tactics Scales, Parent-Child version. Raw search counts from the Google Trends data were estimated using Comscore. Of all 33 search terms, 28 terms showed increases in counts after the lockdowns began. These findings indicate a strong increase in internet searches relating to occurrence, causes, or consequences of emotional and physical maltreatment since the lockdowns began and call for the use of maltreatment-related queries to direct parents or children to online information and support.